Dynamic Radiographs in Assessing Stability of Cervical Spine Fractures: A Multicentre Study. (21st October 2022) - Thumbadoo, Ruben Patrick; Herzog, Jan; Bhamber, Niv; Lupu, Cristina; Kwan, Kenny; Clarke, Andrew; Hutton, Michael; Bernard, Jason; Bishop, Timothy; Lui, Darren F.
Abstract : Background: In the management of a trauma patient with cervical spine injury, the need for accurate diagnostic imaging is key to ensure correct management. Different classification systems have been developed including the Subaxial Injury Classification (SLIC) system and AO cervical spine fracture classification. Through a multicentre study, we have identified a group of cases where the use of CT alone to classify fractures by either SLIC or AO score may be deficient and the use of dynamic cervical spine radiographs could help identify instability. Methods: Three level 1 trauma centers retrospectively reviewed patients with cervical spine injuries. Cervical spine radiographs (AP and lateral) were undertaken in collar, in all patients with suspected cervical spine injury within 2 weeks, followed by reanalysis of scoring systems. Results: Eleven cases were identified in total, and 72% were male with a mean age of 65 years, with approximately 54% being older than 70 years. All patients reported their pain as severe using the Visual Analogue Scale scale. The predynamic radiograph mean SLIC score was 0.73, which is in contrast to the postdynamic radiograph mean SLIC score of 6. The statistical significance ( P = 0.004) was found using the Wilcoxon signed-rank test. Conclusion: Supine imaging eliminates the gravitational loads normally exerted on the c-spine. The cases show assumed cervical stability based on CT, but dynamic c-spine radiographs subsequently demonstrated instability. Therefore, we suggest a combination of SLIC and AO classification using radiologic imaging to classify fracture and correlate clinical symptoms with persistent neck pain, which warrants a Miami-J collar and dynamic c-spine radiograph to assess stability with re-evaluation of scoring.